Toward intersectional and culturally relevant sex and gender analysis in health research. (January 2022) - Rotz, Sarah; Rose, Johnathan; Masuda, Jeff; Lewis, Diana; Castleden, Heather
Abstract: Current institutional frameworks in sex- and gender-based analysis (SGBA) are promising, but significant gaps remain in their relation to recent developments in research praxis. In this paper we draw from our own experiences with a national health research funding agency, the Canadian Institutes of Health Research (CIHR), to critically examine the uptake and implementation of its current frameworks and practices of sex and gender analysis in health research. We conducted semi-structured interviews with a cohort of 18 health researchers alongside an institutional policy analysis to show how sex and gender have been understood, integrated, and addressed within the agency and initiative. Our findings reveal that attention to date has focused on representation (human and data) while deeper justice issues that are attentive to intersectionality, positionality and reflexivity—remain ambiguous. Finally, we discuss possible strategies for institutions to improve the uptake of knowledge, training, and policy to better support intersectional and culturally-relevant frameworks across the diverse research community. Highlights: Research institutes are taking up new concepts and frameworks of sex and gender analysis. We examine whether sex and gender frameworks are attending to power and knowledge production. Intersectionality positionality and reflexivity remain underdressed in sex and gender analysis.